2005
DOI: 10.1074/jbc.m410393200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Responses of Escherichia coli to S-Nitrosoglutathione under Defined Chemostat Conditions Reveal Major Changes in Methionine Biosynthesis

Abstract: Nitric oxide and nitrosating agents exert powerful antimicrobial effects and are central to host defense and signal transduction. Nitric oxide and S-nitrosothiols can be metabolized by bacteria, but only a few enzymes have been shown to be important in responses to such stresses. Glycerol-limited chemostat cultures in defined medium of Escherichia coli MG1655 were used to provide bacteria in defined physiological states before applying nitrosative stress by addition of S-nitrosoglutathione (GSNO). Exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
157
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(167 citation statements)
references
References 50 publications
8
157
2
Order By: Relevance
“…The effect of NO on respiration in J96∆norV was similar to the effects observed in J96wt suggesting that NorV activity is not important for NO detoxification in UPEC during the present conditions. In line with our findings, deletion of norV showed little effect on NO consumption in a non-pathogenic E. coli in aerobic conditions [6,19] Previously, a DNA-based microarray has shown that hmp was among the top 50 genes up-regulated in UPEC strain CFT073 in a mouse UTI-model [44]. Moreover, increased transcription of hmp and norV was reported in an asymptomatic bacteriuria E. coli strain from three patients based on microarray analysis [45].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The effect of NO on respiration in J96∆norV was similar to the effects observed in J96wt suggesting that NorV activity is not important for NO detoxification in UPEC during the present conditions. In line with our findings, deletion of norV showed little effect on NO consumption in a non-pathogenic E. coli in aerobic conditions [6,19] Previously, a DNA-based microarray has shown that hmp was among the top 50 genes up-regulated in UPEC strain CFT073 in a mouse UTI-model [44]. Moreover, increased transcription of hmp and norV was reported in an asymptomatic bacteriuria E. coli strain from three patients based on microarray analysis [45].…”
Section: Discussionsupporting
confidence: 86%
“…Respiratory inhibition in response to NO is well established in non-pathogenic E. coli [3,6,43]. Respiration of UPEC was also significantly inhibited by NO and the inhibition was initiated momentarily upon NO addition and resumed after the NO levels decreased.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Several regulatory proteins have been shown to be sensitive to NO in vitro or in vivo, or both, and so may mediate adaptive responses to NO exposure. These include SoxR, OxyR, FNR, MetR, and Fur (5,6,10,12,17), though in each case the principal function of the regulator is to sense another signal (superoxide, hydrogen peroxide, oxygen, homocysteine, and iron, respectively). The only regulator known to serve exclusively as an NO sensor in E. coli is NorR, which activates transcription of the norVW genes encoding the flavorubredoxin and associated flavoprotein that together reduce NO to nitrous oxide (7,13,14,16,18).…”
mentioning
confidence: 99%
“…Three studies have made use of microarrays to evaluate the response of the E. coli transcriptome to exposure to NO or other reagents that cause nitrosative stress (12,21,27). These experiments differed in their choice of medium (rich or defined), growth conditions (aerobic or anaerobic, batch or continuous culture) and the reagents used to impose nitrosative stress (S-nitrosoglutathione, acidified nitrite, or aqueous NO), which may in part account for the different gene sets identified in each case.…”
mentioning
confidence: 99%